Prognostic Modeling for Bone Sarcomas Based on a Large Prospective Cohort From a Tertiary Care Cancer Center in India - Jyoti Bajpai; Laboni Sarkar; Sushmita Rath; Akash Pawar; Arun Chandrashekharan; Goutam Panda; Dharmpal Jakar; Jaya Ghosh; Siddhartha Laskar; Bharat Rekhi; Nehal Khanna; Jifmi Jose; et al. (JCO Global Oncology)
PURPOSEOutcomes of adolescents and young adults (AYA) with bone sarcomas including osteosarcoma (OGS) and Ewing sarcoma (ES) are affected by various factors including inadvertent previous treatment and poor compliance. We aimed to develop a risk-scoring system derived and validated at a tertiary care cancer center in India.METHODSAll AYA OGS and ES cases treated at our institute with OGS-12 and Ewing’s family of tumors-2001 (EFT-2001) protocols from 2011 to 2021 and 2013 to 2018, respectively, were prospectively analyzed. Weighted scores provided to each prognostic variable on the basis of approximate ratios of the beta coefficients of each factor in the multivariable model were summated to divide patients into three clinically discriminatory risk groups, validated by applying separately to derivation, validation, and whole cohorts.RESULTSAmong 606 (81.0%) of 748 AYA with nonmetastatic OGS, significant factors included in the prognostic model were failure to complete protocol (hazard ratio [HR], 2.65), previous treatment (HR, 2.93), necrosis <90% (HR, 1.63), joint involvement (HR, 2.0), and serum alkaline phosphatase >median (204 U/L; HR, 1.63). Of 104 (39.5%) of 263 AYA with ES, significant factors were failure to complete protocol (HR, 2.84), previous treatment (HR, 6.37), necrosis <100% (HR, 8.73), and tumor size >8 cm (HR, 2.64). For 142 (38.8%) of 366 AYA with metastatic OGS, significant factors were failure to complete protocol (HR, 5.29), metastases not amenable to local treatment (HR, 1.96), necrosis <90% (HR, 1.96), and >10 metastases (HR, 2.44). For 38 (43.6%) of 82 AYA with metastatic extremity ES, significant factors were failure to complete protocol (HR, 3.88) and metastases not amenable to local treatment (HR, 10.6).CONCLUSIONWe developed simple, effective prognostic models for AYA with bone sarcomas with specific potential relevance for low- and middle-income countries.